A checklist of the millipedes (Diplopoda) of Myanmar, with an updated list of Leonardo Fea’s collecting localities - Likhitrakarn, Natdanai; Jirapatrasilp, Parin; Golovatch, Sergei I.; Panha, Somsak (Zootaxa, 2017)
At present, the millipede fauna of Myanmar comprises 92 species from 34 genera, 13 families and 8 orders, mostly described in 1889–1896. All literature records are cited with updates on species identities, as well as numerous taxonomic problems which make the number of species and even genera still imprecise. The Myanmar millipede fauna contains 70 endemic and five widespread synanthropic species. One species is found to have erroneously been recorded from Myanmar, and is ejected from the list of Myanmar millipedes also because of its uncertain taxonomic status. A complete bibliography on the millipedes of Myanmar, an updated list of the collecting localities and a map of the journeys of Leonardo Fea, the principal collector of Diplopoda in Burma, are also presented.